Rape myth acceptance among college students in India: prevalence and predictors in a changing context - Qureshi, Hanif (Deviant behavior, 2021)
In recent years, India has been marked by highly publicized cases of rape that have led to public outcry and demands for rape-law reform and the protection of women. In this context, the purpose of this study is to assess the extent to which rape myths persist in Indian society and to examine the sources of those beliefs. Based on a survey of 55 items drawn from prior research, a sample of Indian college students (N = 910) showed widespread acceptance of these beliefs. Both male and female respondents endorsed rape myths, though acceptance was higher among males and some items were more accepted than others. Responses to a subset of items included in past studies revealed that students in India agreed with rape myths more than their U.S. counterparts. Finally, multivariate analyses indicated that beyond demographic characteristics, rape myth acceptance was heightened not only by sexist attitudes but also by two measures of criminal propensity-antisocial attitudes and low self-control.